RANCANG BANGUN ALAT PENCUCI WORTEL MEKANIS (Design and Construction of Carrot Washer) - John Frienta Meliala; Achwil Putra Munir; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Carrots are plants that contain vitamins and minerals. Carrot washing is the process of removing some microorganisms on carrots that are dirty. This research is about designing, making, testing, and analyzing economical value of carrot washing tool. The parameters observed were effective capacity, and economic analysis. This research were conducted from September 2015 to Mei 2016 at the laboratory Agriculture Engineering, Faculty of Agriculture, Universitas Sumatera Utara.The results showed that the effective capacity of the tool was 30.30 kg / hour, while the economic analysis showed that the cost of the principal for the first year until the fifth year was Rp. 356,40 / kg, Rp. 357.37 / kg, Rp. 358.40 / kg, Rp. 358.48 / kg and Rp. 360,64 / kg. The break even point (BEP) value is 7,830 kg / year, 7,700 kg / year, 8,038 kg / year, 8,393 kg / year and 8,772 kg / year respectively for the first year until the fifth year. Internal rate of return (IRR) is 38.62%. Keywords : Carrot, Washer. ABSTRAK   Wortel merupakan tanaman yang mengandung vitamin dan mineral. Pencucian wortel adalah proses menghilangkan sebagian mikroorganisme pada wortel yang sudah kotor. Penelitian ini adalah mengenai merancang, membuat, menguji, serta menganalisis nilai ekonomis alat pencucian wortel. Parameter yang diamati yaitu kapasitas efektif alat dan analisis ekonomi. Penelitian ini dilaksanakan pada bulan September 2015 hingga Mei 2016 di Laboratorium Keteknikan Pertanian Fakultas Pertanian Universitas Sumatera Utara. Hasil penelitian menunjukkan bahwa kapasitas efektif alat adalah sebesar 30,30 kg/jam, sementara analisis ekonomi menunjukkan bahwa biaya pokok untuk tahun pertama sampai tahun kelima berturut-turut yaitu Rp. 356,40/kg, Rp. 357,37/kg, Rp. 358,40/kg, Rp. 358,48/kg dan Rp. 360,64/kg. Nilai titik impas (BEP) adalah sebanyak 7.830 kg/tahun, 7.700 kg/tahun, 8.038 kg/tahun, 8.393 kg/tahun dan 8.772 kg/tahun berturut-turut untuk tahun pertama hingga tahun kelima. Internal rate of return (IRR) adalah sebesar 38,62%. Kata Kunci : Wortel, alat pencuci.